Iluminado Lucente - Salazar, Victoria S. (Leyte-Samar Studies, 1967)
"Iluminado Lucente, "prince of Leyte lyric poets," dramatist, editor, dedicated public servant, and social critic, occupies a preeminent place in the history of the literature of Leyte. He has with good reason also been called "The Voice of Waray." While his compatriots were writing down their best throughts in borrowed Spanish and English, Lucente, who like Milton "had a jealous love for his mother tongue," struck off on his own in the vernacular of Eastern Leyte and Samar and in so doing earned an imperishable name for himself in the literature of his native province."